Sobre la existencia de una novela policíaca española : un breve repaso a sus principales títulos, autores e hitos - Parra Sánchez, Diego Ernesto (Acta Hispanica, 2015)
This article intends to reflect on the convenience or inconvenience of talking about Spanish detective novel as a solid and influential crime novel trend as the British, the French or the U. S. crime fiction trends. With this aim, apart from having a look to the main arguments either in favor or against this consideration, this work delves into the most important titles and the most representative authors, on the one hand, and into the political, social and economical events which have surrounded the Spanish crime fiction from its origin.